Glee : the beginning - Lowell, Sophia (New York, NY : Little, Brown and Company, 2010)
A prequel to the television show explores what happened before Mr. Schuester took over the glee club, showing the beginning of Puck and Quinn's romance and how the club functioned without its leader.
"An original novel."
"Based on the series created by Ryan Murphy & Brad Falchuk & Ian Brennan."
Keywords: High school students -- Juvenile fiction; Choirs (Music) -- Juvenile fiction